The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jbt.20374
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of DNA binding and cell cycle phase perturbation by the dinuclear complex of Cd(II) with the condensation product of 2‐acetylpyridine and malonic acid dihydrazide N′,N2‐bis[(1E)‐1‐(2‐pyridyl)ethylidene]propanedihydrazide

Abstract: Organometallic Cd(II) compounds have recently attracted attention for their anticancer activity. The interaction of the dinuclear complex of Cd(II) with the condensation product of 2-acetylpyridine and malonic acid dihydrazide, N',N'(2) -bis[(1E)-1-(2-pyridyl)ethylidene]propanedihydrazide (Cd(II)H(2) L), with calf thymus DNA (CT-DNA) was monitored by blue shift in UV-vis spectra of the complex. The binding constant of Cd(II)H(2) L complex with CT-DNA was determined (K(B) = 1.8 × 10(4) M(-1) ) and was indicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In cancer cells, Cd was found to decrease the proportion of cells in the G2/M phase, and induce apoptosis, resulting in a substantial decrease in the number of viable cells [33,34]. Several studies have revealed that the cellular damage induced by 5-FU involves a loss or accumulation of cells in the S phase, G2/M block, and G1/S arrest [35].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, Cd was found to decrease the proportion of cells in the G2/M phase, and induce apoptosis, resulting in a substantial decrease in the number of viable cells [33,34]. Several studies have revealed that the cellular damage induced by 5-FU involves a loss or accumulation of cells in the S phase, G2/M block, and G1/S arrest [35].…”
Section: Discussionmentioning
confidence: 99%
“…The value lies in the range characteristic for binding by intercalation [37], but the steric clashes with DNA exterior caused by the second ligand bound to Co(III) dictates its DNA-binding mode to be surface binding to minor groove. The value differs for one order of magnitude from previously investigated Cd(II) complex with H 2 L which was characterized as minor groove binder [11]. High value of the binding constant for a minor groove binder might be a consequence of the helicoidal geometry of the complex (Fig.…”
Section: Dna Binding Studiesmentioning
confidence: 91%
“…The heptacoordinated binuclear Cd(II) complex with H 2 L showed very good cytotoxic activity already in the low micromolar range [8]. The activity was, at least in part, a consequence of strong binding to DNA [11]. These promising results prompted us to evaluate if other analogous metal complexes exhibit similar behavior.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A major interest of our research group is devoted to metal complexes of polydentate dihydrazone ligands [1][2][3][4][5], mainly because some of these complexes display substantial cytotoxic activity [2][3][4]. While searching for new ligands we have focused our attention on those that combine both hard and soft donor atoms [6][7][8][9][10][11], in particular the heterofunctionalised phosphines, where the phosphorus is the soft donor, and the hard donor is either an oxygen or nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%